Tracheotomy When and Where? - Klemm, Eckart (Tracheotomy and Airway, 2020)
The time for elective tracheotomies has been discussed for years in what has become very comprehensive literature by now. In this chapter, studies with high levels of evidence are taken into account and recommendations are given for the timing of tracheotomies in long-term ventilated patients, with the individual decision being at the center of consideration. Tracheotomies can be performed both in the operating room and in an intensive care unit. The criteria for such choice are presented under interdisciplinary medical and organizational aspects.